Gender difference in the association between volunteering and health-related quality of life among hearing-impaired older adults in China - Xueqing Wang; Dan Zhao; Jingjing Luo; Xuehong Wang; Jingjie Sun; Zhuo Chen; Chengchao Zhou (BMC Geriatrics)
Abstract Background The present study aims to assess the relationship between volunteering and health-related quality of life (HRQoL) among older adults with hearing impairment, as well as the gender difference in this association. Methods We use data from the sixth Health Service Survey of Shandong Province, China. The survey interviewed 35,264 respondents, from which a total of 1,457 hearing-impaired older adults were included in the study. Tobit regression models were used to identify the association between volunteering and HRQoL and gender difference in the relationship. Results The prevalence of volunteering in men and women was 24.05% and 22.20%, respectively. Women had higher EQ-5D utility valuesand VAS scores than men. After controlling potential confounders, participating in volunteering had a significant and positive association with higher HRQoL among older women, while this relationship was not significant for men. The regression model showed the interaction term of gender and volunteering had a significant association with HRQoL. Conclusion The findings suggest volunteering is significantly associated with HRQoL among older adults with hearing impairment, and the association differed by gender. Gender differences should be considered when implementing targeted and appropriate interventions to improve HRQoL among hearing-impaired older adults.